Atmosphere-Ocean Coupled Variability in the Arabian/Persian Gulf - Al Senafi, Fahad (Frontiers in Marine Science, 2022)
The Arabian Gulf comprises one of the world’s most unique and fragile marine ecosystems; it is susceptible to the adverse effects of climate change due to its shallow depth and its location within an arid region that witnesses frequent severe atmospheric events. To reproduce these effects in numerical models, it is important to obtain a better understanding of the region’s sea surface temperature (SST) variability patterns, as SST is a major driver of circulation in shallow environments. To this end, here empirical orthogonal function (EOF) decomposition analysis was conducted to investigate interannual to multidecadal SST variability in the Gulf from 1982 to 2020, using daily Level 4 Group for High Resolution SST (GHRSST) data. In this way, three dominant EOF modes were identified to contribute the Gulf's SST variability. Significant spatial and temporal correlations were found suggesting that throughout the 39-year study period, SST variability could be attributed to atmospheric changes driven by the El Niño-Southern Oscillation (ENSO), Atlantic Multidecadal Oscillation (AMO), and Indian Ocean Dipole (IOD) climate modes. Spatial and temporal analyses of the dataset revealed that the average SST was 26.7 oC, and that the warming rate from 1982 to 2020 reached up to 0.59 oC/decade. A detailed examination of SST changes associated with heat exchange at the air-sea interface was conducted using surface heat fluxes from fifth generation (ERA5) European Centre for Medium-Range Weather Forecasts (ECMWF). Despite the SST warming trend, the accumulation of heat during the study period is suggesting that there was an overall loss of heat (cooling). This cooling reverted into heating in 2003 and has since been increasing.